THE IMPROVED EMPLOYMENT AT AZRA HOSPITAL IN BOGOR THROUGH EFFECTIVE INTERNAL COMMUNICATION - Mafriningsianti, Evi (Yayasan Education and Social Center, 2023)
This research aims to examine internal communication efforts to improve employee performance at Azra Hospital in Bogor. At Azra Hospital in Bogor, the study focuses on the dimensions of internal communication: vertical, horizontal, and diagonal. The analytical method used is qualitative analysis with an interactive analysis model involving four steps: data collection, data reduction, data presentation, and conclusion. Data was collected through textbooks, related references, observations, interviews, and field research. According to the study's findings, communication in this hospital is tiered and structured in the vertical communication dimension, but this results in limited communication openness. Submission of ideas and ideas to improve employee performance needs to be enhanced by a long process. This study describes the challenges of optimizing internal communication to improve employee performance at Azra Hospital in Bogor. Recommendations can be provided to enhance transparency in vertical communication, optimize the allocation of time and physical resources for horizontal transmission, and effectively identify suitable instances for implementing diagonal communication in intricate scenarios